Reformulation of Village Head Election Regulations in the Perspective of Legislation - Edhy Hardjito; Zarkasi Zarkasi; Arfa'i Arfa'i (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This research is motivated by the persistent disharmony and lack of vertical synchronization in the regulation of the Village Head Election (Pilkades) within the Indonesian legislative system. Currently, technical implementing regulations frequently deviate from the core spirit of village autonomy and the democratic principles mandated by Law Number 6 of 2014 concerning Villages. This study aims to analyze the current laws regarding Pilkades and formulate an ideal, democratic, and high-integrity regulatory reformulation concept. The method utilized is normative juridical legal research through library research, employing statute and conceptual approaches to evaluate the synchronization of legal norms. The analytical results demonstrate that current Pilkades regulations remain highly centralistic and trigger legal uncertainty. Fundamental problems include the Regent's absolute authority in resolving election disputes (which harms judicial impartiality), supra-village domination in additional candidate selections, undemocratic single-candidate deliberation mechanisms, and outdated central regulations hindering E-Voting innovations. Therefore, a comprehensive reformulation emphasizing village independence is urgently necessary. This reformulation proposes four main designs: transferring dispute resolution to the judicial domain, national legalization of E-Voting, rearranging and limiting supra-village authority, and establishing an independent, legally guaranteed supervisory institution (Panwas Pilkades).